ВЛИЯНИЕ ПОЛИМЕРМЕТАЛЛОКОМПЛЕКСОВ ПЕКТИНА НА РОСТ И РАЗВИТИЕ СЕМЯН ХЛОПЧАТНИКА (Scientific journal of the Fergana State University, 2023)
Complexes based on lemon pectin with cobalt ions, which allow supplementing the lack of microelements in the cotton nutrition of "C-6524" variety, do not violate the basic vital functions of plants.